System of official texts guiding and assuring the execution of law on foreign investment in Vietnam V.1 = Hệ thống các văn bản hướng dẫn và bảo đảm thi hành luật đầu tư nước ngoài tại Việt Nam T.1. (Hà Nội : The statistics publishing house, 1999)
Forms of Investment; Measures of Investment Guarantee; Rights and Obligations of Foreign Investors and Foreign-Invested Enterprises...
Keywords: Pháp luật; Law on foreign investment; Law; Luật đầu tư nước ngoài; Investment -- Regulation; Foreign investment -- Legal; Luật đầu tư